Spontaneous clearance and treatment of acute hepatitis C infection in HIV-positive men with 48 weeks of interferon-alpha and Ribavirin. (March 2013) - Webster, D P; Wojcikiewicz, T; Keller, M; Castelnovo, D; Mistry, H; Gilleece, Y; Tibbie, J; Fisher, M
Acute hepatitis C infection in the context of HIV is an emerging problem in men who have sex with men (MSM). We conducted a retrospective cohort study of MSM diagnosed with and treated for acute hepatitis C infection over 10 years. Genotype 1 was the commonest type representing 69% of cases; the spontaneous clearance rate was 20%. The overall sustained virological response (SVR) rate on an intention-to-treat basis was 83%; SVR and was 92% for those completing 48 weeks of treatment. The presence of detectable RNA at week 12 had a 100% negative predictive value for SVR. This is the largest single cohort treated with 48 weeks of interferon and ribavirin and the treatment SVR is one of the highest reported. We propose that a 48-week treatment regimen may be superior to shorter (24-week) regimens though we acknowledge the need for a randomized controlled trial.